Towards long double-stranded chains and robust DNA-based data storage using the random code system - Yang, Xu; Shi, Xiaolong; Lai, Langwen; Chen, Congzhou; Xu, Huaisheng; Deng, Ming (Frontiers in Genetics, 2023)
DNA has become a popular choice for next-generation storage media due to its high storage density and stability. As we all know, DNA is the storage medium of life information. DNA has significant information storage capacity and low-cost, low-power replication and transcription capabilities. Using DNA long double-stranded for storage can improve information storage density and storage stability. However the long DNA chains will bring about many unstable factors that make it difficult to meet the constraints of biological systems. Here, inspired by the idea of fountain code, we design a highly robust coding scheme, called “random code system”. This system contains these processes, the establishment of random matrix, Gaussian preprocessing, and random equilibrium. Random code (RC) has better robustness and recovery ability of lost information compared with Luby transform codes (LT code). Through biological experiments, 29390Bit data is stored in 25 700bp chains with a storage density of 1.78bit/nt.